P61 Karel Styblo comes to town: staff perspectives on TB cohort review. (2nd December 2011) - Anderson, C; Tamne, S; White, J; Abubakar, I; Anderson, S; Dart, S; DeKoningh, J; Lipman, M
Abstract : Since its creation by Dr Karel Styblo, the cohort review (CR) principle of systematically analysing treatment outcome of every notified TB case and contact investigation in a brief, timely, structured manner, has been implemented widely outside of the UK—with impressive results. In 2010, North Central London (NCL) TB service adopted the concept, trained staff members and put in practice CR. Given the resource implications that our service faced already, plus the potential for its introduction to result in an increased staff workload, we undertook a survey of how CR was perceived and the impact it had on those involved in its use. After four rounds of CR (12 months from introduction), an anonymous on-line survey was sent to NCL staff members plus external participants and observers who had attended at least one review. The survey explored participant's personal and institutional response to the organisation, impact and outcome of CR's introduction. It was sent to 88 individuals. 72 (82%) completed the 10 min online questionnaire. Over 95% felt that CR identified gaps in service, most frequently: collaboration with other TB services (69%), patient care (63%), collaboration with allied services (51%) and service organisation (45%). Just over a third felt that CR highlighted training needs, especially for contact tracing. 70% reported changes to their way of working—in particular altering practice in response to apparent weaknesses in their approach to contact tracing. 86% felt that CR led to improvement in the speed of interventions, better data quality and enhanced professional relations. A small number of staff noted negative consequences which largely reflected increase in initial work load. Cohort review has enhanced our service provision. It is well received by local staff as well as external participants & observers. Our data are encouraging; and we hope will assist in promoting roll out to other parts of the country.